The effects of mid-Holocene fluvio-eolian interplay and coastal dynamics on the formation of dune-dammed lakes in NE Brazil. (15th September 2018) - Zular, André; Utida, Giselle; Cruz, Francisco W.; Sawakuchi, André O.; Wang, Hong; Bícego, Márcia; Giannini, Paulo C.F.; Rodrigues, Selma I.; Garcia, Guilherme P.B.; Vuille, Mathias; Sifeddine, Abdel; Zocatelli, Renata; et al.
Abstract: We analyzed the Late Quaternary coastal evolution of the easternmost tip of South America in Brazil in light of fluvial-eolian interactions controlled by relative sea-level, climate, and coastal physiography changes. The chronology obtained by OSL-SAR of 36 samples coupled with sedimentological analysis from stabilized dunes suggest that eolian activity was primarily controlled by episodes of sediment availability because prevailing SE trade winds have been steadily strong throughout the Holocene. Contrary to the most conventional view linking dune activity to aridity, dune buildup occurred in a period of increased humidity in NE Brazil between 11 ka and 6 ka when a rising relative sea level and higher rainfall enhanced sediment delivery benefiting the construction of transgressive dunefields. The interplay of these advancing dunes with the existing drainage pathways is here investigated using a modern regional analog and through the evolution of Boqueirão Lake formed by dune blockage. Analysis of a sediment core from this lake dated between 8.4 and 0.9 ka indicated changes over time in microfossil assemblages, organic geochemistry, and grain size data conforming to fluvial or lacustrine depositional conditions. Between 7.2 and 4.4 ka, during the predominantly regional humid climate, the high abundance of fluvial sponge species correlated with a framework of competent-flow drainage systems diverting from advancing dunes. An abrupt transition from a wetter to a drier climate at 4.4–4.0 ka stimulated episodes of fluvial damming as indicated by sharp changes from sandy to muddy sediments and anomalous concentration of sponge spicules concurrent with significant mortality rates of fluvial adapted species. From 3.9 ka to the present, the disappearance of sponge spicules and peaking diatom concentration attested to a predominant lacustrine environment. Thus, the formation of Boqueirão Lake is mainly a result of the regionally drier climate and not a consequence of increased humidity in coastal NE Brazil. Highlights: Dune buildup occurred along increased humidity in NE Brazil between 11 ka and 6 ka. Sediment supply was also favored by a rising sea level. Fluvio-eolian interplay favored the formation of Boqueirão Lake under regionally drier climate.